"From local island energy to degrowth? Exploring democracy, self-sufficiency, and renewable energy production in Greece and Spain". (November 2021) - Tsagkari, Marula; Roca, Jordi; Kallis, Giorgos
Abstract: The energy sector is at the center of the current economic system, and of literature and activism on degrowth, which questions the sustainability of current models of energy use. Local and small-scale energy systems may have the potential to reduce energy and resource consumption and to advance degrowth-related ideals of energy democracy, self-sufficiency, and local production. In the present paper we link a discussion on degrowth and local energy projects, using two case studies from southern European islands, El Hierro in Spain, and Tilos in Greece. These pioneer local energy initiatives have a complex ownership model that includes various public and private actors, and aspirations that go beyond merely electricity production to other economic and social goals. We look into the promise of these initiatives in transforming insular areas and promoting an alternative way of living, comparing attributes of the processes involved to four degrowth principles. We conclude that despite the degrowth potential of these local energy projects, their prospects are limited to revitalizing local economies and empowering local communities, but not necessarily reducing energy use or creating an alternative to the growth orientation of the islands.